Immediate Postoperative Pelvic Organ Prolapse Quantification Measures and 2-Year Risk of Prolapse Recurrence. Issue 4 (October 2020) - Siff, Lauren N.; Barber, Matthew D.; Zyczynski, Halina M.; Rardin, Charles R.; Jakus-Waldman, Sharon; Rahn, David D.; Smith, Ariana L.; Mazloomdoost, Donna; Sridhar, Amaanti; Gantz, Marie G.
Abstract : OBJECTIVE: To assess whether resting genital hiatus, perineal body, and total vaginal length measured intraoperatively at the conclusion of surgery are associated with prolapse recurrence 2 years after native tissue pelvic organ prolapse reconstruction. METHODS: This ancillary analysis of the OPTIMAL (Operations and Pelvic Muscle Training in the Management of Apical Support Loss) trial included women who had an immediate postoperative pelvic organ prolapse quantification (POP-Q) examination and 2-year follow-up. Primary outcome was bothersome bulge symptoms. Secondary outcomes were anatomic failure, surgical failure (either anatomic failure or bothersome bulge symptoms), and sexual function. Descriptive statistics assessed relationships between postprocedure POP-Q measures and these four outcomes. Multivariable models were fit to the data to control for baseline differences in bivariate comparisons. Receiver operating characteristic curves were generated to identify an optimal genital hiatus cut point associated with bothersome bulge, and this threshold was explored. RESULTS: This analysis included 368 participants. Bivariate analyses identified age, body mass index, vaginal deliveries, baseline genital hiatus, perineal body, and advanced POP-Q stage (3 or higher vs 2) as clinically relevant variables to include in multivariable models. After adjusting for these variables, the association between immediate postoperative genital hiatus and bothersome bulge (adjusted odds ratio [aOR] 1.4; 95% CI 0.9–2.1) was not significant at the P <.05 level; however, immediate postoperative genital hiatus was associated with anatomic (aOR 1.6; 95% CI 1.1–2.3) and surgical failure (aOR 1.5; 95% CI 1.0–2.1). Immediate postoperative genital hiatus of 3.5 cm was the selected cutoff (area under the curve 0.58, 95% CI 0.50–0.66 from the bothersome bulge model). Women with genital hiatus 3.5 cm or greater were more likely to have anatomic and surgical failures at 2 years. No POP-Q measures were correlated with 2-year sexual function. CONCLUSION: A larger immediate postoperative genital hiatus measurement of 3.5 cm or greater is not associated with bothersome bulge symptoms or sexual dysfunction but is associated with anatomic and surgical failures 2 years after native tissue vaginal reconstructive surgery. Abstract : Larger immediate postoperative genital hiatus (3.5 cm or greater) is not associated with 2-year bothersome bulge symptoms or sexual dysfunction but is associated with anatomic and surgical failures after vaginal reconstruction.